Question d'honneur Les notions d'honos, honestum et honestas dans la République romaine antique - Jacotot, Mathieu (Publications de l'École française de Rome, 2019)
Is it legitimate to use the modern notion of "honor" in connection with the ancient Roman Republic? Did the Romans of that time follow a strict code of conduct? On what did they base social prestige? What marks of distinction did they use and for what purposes? These are some of the questions this book attempts to answer. To do this, the author analyzes three Roman notions, honos , honestum and honestas, which cover socio-political objects (marks of honor, prestige, public office) and moral data (dignity of conduct, good ethics). This diversity is apprehended in the work by a plural approach, relating to semantics, sociology and the history of ideas. The preliminary study of the meaning of these terms in the Latin texts thus leads to the examination of the practices of homage and honor in the life of the Romans. Then confronting practice with theory, the work examines the way in which these three notions were employed as literary themes, ideological instruments and philosophical concepts among the Latin authors of the Republic.